10.1001/jama.2012.5833.test (CrossRef Listing of Deleted DOIs, 2000)
IMPORTANCE: Despite existing prevention strategies, infections remain a major cause of morbidity and mortality in children in Africa with sickle cell anemia. OBJECTIVE: To determine the safety and effectiveness of daily zinc supplementation to prevent all-cause infection in children with sickle cell anemia in Uganda. DESIGN, SETTING, AND PARTICIPANTS: A randomized, double-blind, placebo-controlled trial of children aged 1.00 to 4.99 years with sickle cell anemia at Jinja Regional Referral Hospital in Jinja, Uganda, from February 10, 2025, to April 30, 2025, with 6 months of follow-up through November 7, 2025. INTERVENTIONS: Participants received zinc sulfate at 20 mg daily or placebo daily for 6 months. MAIN OUTCOMES AND MEASURES: The primary outcome was all-cause infections per 100 person-years, using standardized clinical criteria to define infections. RESULTS: Among 118 children screened for eligibility, 100 were randomly assigned to receive zinc supplementation (n = 50) or placebo (n = 50) (mean [SD] age, 36.0 [13.2] months; 45 female [45%]). At enrollment, 45 participants (45%) were receiving hydroxyurea therapy. All participants initiated or continued receiving hydroxyurea after enrollment. During the 6-month follow-up, there was complete ascertainment for all participants and no loss to follow-up. There were 80 all-cause infections in the zinc group and 124 in the placebo group, corresponding to a significantly lower infection rate in the zinc group than the placebo group (305.7 [95% CI, 242.4-380.4] infections per 100 person-years vs 480.7 [95% CI, 399.8-573.1] infections per 100 person-years; rate difference, -176.0 [95% CI, -300.8 to -51.3]; incidence rate ratio after adjustment for baseline age, sex, and hydroxyurea use, 0.62 [95% CI, 0.45-0.86]). No adverse events requiring discontinuation of the study intervention were observed in either group. CONCLUSIONS AND RELEVANCE: Zinc supplementation at 20 mg per day reduced all-cause infection in children with sickle cell anemia younger than 5 years in Uganda. Multisite clinical trials are needed to validate these findings and to assess effectiveness in older children. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT06561061.